'Kawaii' culture evaluation in Malaysia - Abdul Rahman, Julaila; Md Fudzee, Farhana; Furuya, Shigeru (2014)
Japanese kawaii culture has been popular throughout the world recently. It influences the socio-economy in areas of fashion, tourism, transportation, etc. which can be seen clearly. In Malaysia, the kawaii culture is getting popular among young people through the fashion. The research aim is to observe the Malaysian understanding on Japanese kawaii culture in two kinds of surveys. In both surveys, the samples of fashion were selected and arranged in paired for evaluation to get its categorization of intimacy among all the samples. Collected data for both surveys were analyzed by Mds and cluster analysis. The first survey is to study the Malaysian understanding on Japanese kawaii fashion. Thirty kinds of samples of Japanese fashion were selected. As a result, four kinds of groups of kawaii Japanese fashion were obtained, which were ‘stylish’, ‘teen’, ‘rare’ and 'ayu'. The next survey is to study the recent kawaii fashion in Malaysia. Twenty two kinds of samples of Malaysian kawaiii fashion were selected. The results showed that ayu, adult, boyish and street-look were the groups.As the conclsion, it can be said that in both surveys, Malaysian understood the kawaii image of fashion contains the ayu element. Japanese kawaii fashion was more towards the teenagers, while Malaysian kawaii fashion was more towards the adult style. Japanese kawaii fashion was evaluated as a new trend, while Malaysian kawaii fashion is more to daily attire; boyish and street-look. Kawaii culture has been innovated to be suited to Malaysians' own style and look, which has the religous consideration. Kawaii culture in Malaysia is one of the good subculture that can be developed more to enhance the economy growth.